Ação civil pública, jurisdição processual e desastres ambientais antropogênicos na sociedade em rede - Gasparetto, Hígor Lameira (2022)
The network society is increasingly complex and dynamic. In it, all types of interaction are transformed, and the law must be able to protect them. Likewise, the risks are increasing and are related to the set of actors and factors interacting in globalization, leading to catastrophic events. Hence, instruments are needed to adequately protect and repair these disasters that ultimately reach the Judiciary; it is in this context that public civil action stands out. Thus, this investigation examines public civil action as a special procedure to protect environmental law in the context of the network society and its limitations from a critical-reflexive perspective. For this, this study is based on philosophical hermeneutics, limiting itself to understanding the procedural insufficiency of public civil action and the necessary construction of correct answers in the face of the ideals of the Democratic State of Law. Given the theme and its limitation, this paper aims to investigate the effectiveness of public civil action as a procedure for the protection and repair of the right to disasters, considering its imprisonment to the rational liberal-individualistic paradigm and necessary construction of correct answers in its universe in order to answer the following question: What are the conditions for it to be possible to speak of the effectiveness of public civil action in procedural and substantial aspects as a locus of repair of anthropogenic environmental disasters, such as in the cases of the Mariana and Brumadinho environmental disasters? To answer the problem, methodologically, this study employed a phenomenological-hermeneutic approach, not speaking of a method per se, but of a way of being-in-the-world based on what Heidegger and Gadamer teach, with language being a condition for the insertion of the subject in this world. The procedure consisted of bibliographical and documental research and employed judiciary records and abstracts as the technique. Furthermore, philosophical hermeneutics were used as the basis with Streck’s Critical Hermeneutics of Law as a conductor, according to Heidegger and Gadamer. Based on this configuration, this work is structured in two chapters divided into three subchapters, concluding that legislative change is necessary for the procedural aspect. As long as the change does not occur in such a way as to reorganize the structure of the lawsuit, it will continue to perish when faced with cases such as those addressed herein. Substantially, the condition for being able to discuss effectiveness is the guarantee of correct answers, and this is because judicial decisions must be complete, coherent, and handed down by impartial individuals who respect its dual dimension.